Dipolar cations confer defect tolerance in wide-bandgap metal halide perovskites - Hairen Tan (Nature Portfolio, 2018)
The performance of wide-bandgap perovskite photovoltaics is limited by the undesired phase transition and high density of deep level traps. Here, Tan et al. incorporate dipolar methylammonium cation to make the material defect-tolerant and achieve a high power conversion efficiency of 20.7%.